2007
DOI: 10.1101/gad.421807
|View full text |Cite
|
Sign up to set email alerts
|

A novel checkpoint mechanism regulating the G1/S transition

Abstract: Ultraviolet irradiation of fission yeast cells in G1 phaseinduced a delay in chromatin binding of replication initiation factors and, consistently, a transient delay in Sphase entry. The cell cycle delay was totally dependent on the Gcn2 kinase, a sensor of the nutritional status, and was accompanied by phosphorylation of the translation initiation factor eIF2␣ and by a general depression of translation. However, the G1-specific synthesis of factors required for DNA replication was not reduced by ultraviolet r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 32 publications
7
69
0
7
Order By: Relevance
“…1 C and D). These data show, as seen before (10), that the cells delay S-phase entry for more than 30 min in response to UVC irradiation and that the three parameters give consistent reports on cell-cycle progression. The phosphorylation of eIF2α was monitored as a measure of Gcn2 activation and it coincided with the length of the cell-cycle delay (Fig.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…1 C and D). These data show, as seen before (10), that the cells delay S-phase entry for more than 30 min in response to UVC irradiation and that the three parameters give consistent reports on cell-cycle progression. The phosphorylation of eIF2α was monitored as a measure of Gcn2 activation and it coincided with the length of the cell-cycle delay (Fig.…”
Section: Resultssupporting
confidence: 65%
“…We have shown that fission yeast cells delay entry into S phase after UVC irradiation by a Gcn2-dependent mechanism (10). Here, we demonstrate that this radiation-induced delay in G 1 phase depends on processing of the DNA damage.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Control of pre-replication complex stability has previously been suggested as a critical component in regulation of S-phase initiation during SAM-limitation in budding yeast 19 and in response to UV-irradiation in fission yeast. 33 Pre-replication complex assembly might thus represent an underappreciated cell cycle checkpoint target that could be particularly important to link cell proliferation with cellular metabolites. Our results suggest that SAM is the critical mediator of cancer cell methionine dependency, and it is tempting to speculate that the pathway we describe represents a cell cycle checkpoint that ensures epigenetic stability by preventing S-phase during limited SAM availability.…”
Section: Discussionmentioning
confidence: 99%